Survey on anomaly detection technology based on logs - Yingjun ZHANG; Ushangqi LI; Mu YANG; Haixia ZHANG; Kezhen HUANG (网络与信息安全学报)
Log information has become an important information resource in the rapid development of information systems.Through the analysis of logs,abnormal detection,fault diagnosis and performance diagnosis can be performed.The log-based anomaly detection technology was focused on.Firstly,the currently used log-based anomaly detection framework was introduced,and then the key link technologies such as log analysis and log anomaly detection were focused on.Finally,the current technology was summarized and suggestions for future research directions were given.